Decision Intelligence: Creating a Fit between Intelligence Requirements and Intelligence Processing Capacities. (July 2021) - Moser, Roger; Rengarajan, Srinath; Narayanamurthy, Gopalakrishnan
Dynamic business environments throw up many challenges for senior executives. To make strategic decisions in such environments, it is crucial for them to find the right fit between the intelligence required for decisions, and how their companies gather and process intelligence. This paper conceptualizes a ' Decision Intelligence ' framework for achieving such a fit. The four major elements constituting the framework place the emphasis explicitly on senior executives adopting the right decision context, tailoring appropriate decision-making frameworks, innovating the access to diverse sources of intelligence and implementing the decisions proficiently. These elements are illustrated and elucidated by drawing on multiple firm experiences from automotive, agritech, pharma, banking and farming sectors. The paper concludes with a discussion on the major implications on intelligence processing capacity challenges of companies, and what this implies for management education and strategy research.